2003
DOI: 10.4049/jimmunol.171.7.3348
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: CD28 Controls Peripheral Homeostasis of CD4+CD25+ Regulatory T Cells

Abstract: CD28/B7 blockade leads to exacerbated autoimmune disease in the nonobese diabetic mouse strain as a result of a marked reduction in the number of CD4+CD25+ regulatory T cells (Tregs). Herein, we demonstrate that CD28 controls both thymic development and peripheral homeostasis of Tregs. CD28 maintains a stable pool of peripheral Tregs by both supporting their survival and promoting their self-renewal. CD28 engagement promotes survival by regulating IL-2 production by conventional T cells and CD25 expression on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
536
4
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 613 publications
(568 citation statements)
references
References 24 publications
23
536
4
5
Order By: Relevance
“…Blocking the CD28/B7 pathway using CTLA-4 Ig molecule or anti-B7-1/2 Ab has been reported to reduce the number of T reg in both thymus and periphery [4,35]. Bluestone and collaborators [4] demonstrated that CD28 act directly on T reg to sustain their CD25 expression and therefore their response to IL-2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Blocking the CD28/B7 pathway using CTLA-4 Ig molecule or anti-B7-1/2 Ab has been reported to reduce the number of T reg in both thymus and periphery [4,35]. Bluestone and collaborators [4] demonstrated that CD28 act directly on T reg to sustain their CD25 expression and therefore their response to IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…Bluestone and collaborators [4] demonstrated that CD28 act directly on T reg to sustain their CD25 expression and therefore their response to IL-2. Indeed, exogenous IL-2 administration is not able to compensate the absence of CD28 and therefore of the CD25 expression [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regulatory T cells are indeed dependent on CD28 for their development and survival, thus the use of CTLA-4Ig can induce a drastic reduction of this cell population and exacerbate the autoimmune process. 109,110 Despite the intricacies of co-stimulatory modulation, CTLA-4Ig has been developed and tested in patients with autoimmune diseases.…”
Section: Co-stimulatory Blockade Treatments In Human Autoimmune Diseasesmentioning
confidence: 99%